Organoleptic Quality of Gandaria Restructuruted Product using Gelatin - Breemer, Rachel; Pattiruhu, Gysberth (Universitas Pattimura, 2024)
Gandaria is one of the fruits that has a fairly high nutritional content. This gandaria fruit has many functions,one of which is made into gandaria chili sauce and juice. Gandaria fruit is very popular with the public, but the shelf life of this fruit is very short so further handling is needed. One of the handling that can be done is the restructuring of the fruit. This fruit restructuring is one of the food processing processes that is carried out without changing the taste of the product itself. The purpose of this study was to determine the organoleptic quality of gandaria restructuring products. This study used a Complete Randomized Design with 2 factors where factor A was the concentration of Gandaria (75, 100 and 125 grams) and Agar-agar (4, 6 and 8 gr). The results showed that gandaria restructuring at various concentrations of 6 gr agar and 100 gr fruit pulp gave the best gandaria restructuring products with a color preference level of 4.07 (like), taste 3.67 (rather like to like), texture 3,22 (ordinary) and overall (usually towards likes).